The effects of processing variables on the energy absorption of composite crash structures - Turner, Thomas A. (2004)
Environmental pressures are driving automotive manufacturers towards light weight cost efficient structures. Composite materials have been shown to display high specific energy absorption levels thus offering opportunities for mass reduction over conventional steel structures. Whilst composites display these specific advantages, the mechanisms by which energy is absorbed are more complex and are preventing widespread acceptance of composite structures. This work aims to further scientific understanding of the crushing process and provide realistic data for a wide range of processing conditions and commonly used materials.